FeCoNi nanoalloys embedded in hierarchical N-rich carbon matrix with enhanced oxygen electrocatalysis for rechargeable Zn-air batteries. Issue 48 (7th December 2021) - Liu, Jinlong; Luo, Ziyu; Zhang, Xinxin; Zheng, Hailong; Peng, Lei; Qian, Dong; Jia, Chuankun; Sun-Waterhouse, Dongxiao; Waterhouse, Geoffrey I. N.
Abstract : FeCoNi nanoalloys encapsulated by a N-rich hierarchical carbon matrix were fabricated as a highly improved oxygen electrocatalyst for rechargeable Zn–air batteries, due to the unique core–shell structure with favorable electron penetration effect. Abstract : Component optimization and structure engineering are commonly used strategies to realize high-performance electrocatalysts for sustainable energy technologies. Herein, we successfully synthesized FeCoNi nanoalloys embedded in a hierarchical N-rich carbon matrix (FeCoNi@HNC), which served as an efficient and durable electrocatalyst for both the oxygen reduction reaction (ORR) and oxygen evolution reaction (OER) in alkaline media. Experimental investigations and density functional theory (DFT) calculations revealed that the core–shell structure of FeCoNi@HNC was highly beneficial for tuning the adsorption/desorption of oxygen intermediates on the N-rich carbon shell through electron penetration effects, thereby simultaneously delivering outstanding ORR activity (comparable to Pt/C) and OER activity (superior to IrO2 /C). Further, the N-rich carbon shell acted as a barrier to prevent excessive oxidation and dissolution of the FeCoNi alloy nanoparticles, thus imparting FeCoNi@HNC with excellent stability in alkaline electrolytes. A prototype zinc–air battery constructed using FeCoNi@HNC exhibited a maximum power density of 109 mW cm −2 and no obvious increase in the discharge–charge voltage gap over 200 cycles at 5 mA cm −2, vastly superior battery performance to a battery fabricated using Pt/C + IrO2 /C catalysts. Results validate FeCoNi@HNC as a very promising earth-abundant electrocatalyst for rechargeable zinc–air batteries and potentially other energy conversion devices that utilize ORR and OER.